Assessment of the frequency of consumption of selected food products by territory defense soldiers, depending on nutritional knowledge in the context of a healthy lifestyle - Łoboda, Dorota (Journal of Education, Health and Sport, 2023)
Introduction: The problem of rational, proper nutrition that ensures the body's proper performance and quality of work is of particular importance in the army. This is related to the specificity of military service, with a significant physical and mental burden, and this makes it very important to properly meet the nutritional needs of young soldiers, significantly affecting combat ability and mental toughness. The aim of the article is to analyze the frequency of consumption of selected food products and to evaluate the lifestyle of soldiers of the territorial defense forces Objective: The aim of the study was to assess the frequency of consumption of food products by soldiers of the territorial defense forces in connection with lifestyle. Material and methods: The study was conducted among 100 male soldiers of the Territorial Defense Forces, using the KomPAN questionnaire for examining views and eating habits for people aged 16 to 65, from which part B concerning the frequency of food consumption and part C related to lifestyle were selected for the study. Results: With age, the percentage of surveyed soldiers who were found to be overweight increased, while the percentage of soldiers maintaining a normal body weight decreased. In the diet of soldiers there are too few vegetables, fruits and fish, while white bread and sweetened drinks appear too often. The surveyed group believes that the level of their nutritional knowledge is insufficient, while the majority declare that their nutrition is correct Conclusions: Based on the conducted research, it appears that soldiers should continue to be trained and the basic knowledge about proper nutrition should be systematized, including the nutritional prevention of diet-related diseases of civilization. The specificity and requirements of a given military service as well as the soldier's individual health condition should be taken into account.